Preparation of AgNPs/Ca3Co4O9 nanocomposites with enhanced thermoelectric performance. (March 2016) - Lin, Yunzhi; Sun, Suping; Zhang, Qihao; Shen, Hongwei; Shao, Qin; Wang, Lianjun; Jiang, Weihui; Jiang, Wan
Abstract: Ca3 Co4 O9 polycrystalline thermoelectric ceramics with small amounts of silver nanoparticles (AgNPs) have been fabricated by spark plasma sintering (SPS) directly from the mixture of AgNPs prepared by wet chemical method and Ca3 Co4 O9 powders synthesized by solid-state reaction. The effects of AgNPs introducing on the morphology and thermoelectric properties have been investigated in detail. By this route, we achieve a lower thermal conductivity due to the increased phonon scattering, decreasing from 3.1 W/m(Ca3 Co4 O9 ) to 1.6 W/m(AgNPs/Ca3 Co4 O9 ) at 700 K. Besides, the nano-sized AgNPs effectively strengthen the p-type Ca3 Co4 O9 grain orientation (from 0.5 to 0.7), leading to a significant enhancement of the electrical conductivity. As a result, the Ca3 Co4 O9 sample containing 2.0 vol% AgNPs exhibits an exceedingly enhanced ZT value at 700 K, which is about 5 times higher than that of pure bulk Ca3 Co4 O9 . The results demonstrate that introducing nanoparticles as a second nano-phase is a promising route to optimize the thermoelectric performance of Ca3 Co4 O9 .